Post Bariatric Buttock Contouring - Mohamed, Mohamed Tarik; Ali, Ramy Samy (Journal of medical and pharmaceutical sciences, 2019)
The aim of this work is to review the literature aiming at highlighting the thoughtful drawbacks of bariatric surgeries on the buttock region. Together with understanding the best method of contouring this region back to its youthful shape as stated in previous literature. Criteria of searching used a search string to literature dating 1968 till present. Search string used on PubMed to find relevant literature. Search string involved searching for keywords; buttock contouring, post bariatric contouring, buttock lift, post massive weight loss. The repeated literature had been omitted. Exclusion criteria was any literature before 1968; as a mere factor of abundance of literature after then. Literature included was dedicated for post bariatric ptosis correction. After removal of duplicates 74 papers were included in the literature review for 6 months. literature was reviewed in pursuit of the most appropriate technique for post massive weight loss buttock contouring. The prevalence of weight loss surgeries, which has recently occurred as a treatment for the prevalence of obesity, behind the need for treatment of sagging skin around the body, including the buttocks, has been clarified many ways to resolve, including surgical and non-surgical, there is no way like me to treat that problem, but it differs from Individual to another, heavily dependent on the surgeon.
Keywords: buttocks contouring; after obesity treatment; buttock lift; after massive weight loss